2021
DOI: 10.3390/nano11051331
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Smart and Active Biodegradable Packaging Materials

Abstract: Interest in the development of smart and active biodegradable packaging materials is increasing as food manufacturers try to improve the sustainability and environmental impact of their products, while still maintaining their quality and safety. Active packaging materials contain components that enhance their functionality, such as antimicrobials, antioxidants, light blockers, or oxygen barriers. Smart packaging materials contain sensing components that provide an indication of changes in food attributes, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 256 publications
0
44
0
6
Order By: Relevance
“…Examples of improving functionality by enriching film-forming materials are the use of inorganic nanoparticles of iron or silver oxide and organic nanoforms of cellulose and chitosan. Composites enriched in this way show better optical, mechanical and barrier properties and also biological activity [2,6]. The literature data have shown that ginkgo leaf extract has strong antioxidant activity in gelatin membranes.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Examples of improving functionality by enriching film-forming materials are the use of inorganic nanoparticles of iron or silver oxide and organic nanoforms of cellulose and chitosan. Composites enriched in this way show better optical, mechanical and barrier properties and also biological activity [2,6]. The literature data have shown that ginkgo leaf extract has strong antioxidant activity in gelatin membranes.…”
Section: Introductionmentioning
confidence: 94%
“…Food packaging is primarily intended to protect the packed food, preserve it, and enable transport. Edible packaging allows extending of the shelf life of food and maintaining its high quality [2]. There are three types of edible packaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the scientific databases, with keywords of "sustainable marketing" or "green marketing" and "food" or "dairy" and "Internet of Things", proved that even its usefulness is not addressed by the researchers. The most similar to the current issue were two studies about blockchain technology in agri-food supply chains [83] and sustainable technologies in agri-food 4.0 [84], and some more, but only in the area of smart packaging, specifically in the dairy industry [58,85,86]. Therefore, it is worth discussing how to improve supply chain management methods and concepts by using IoT and IoE solutions.…”
mentioning
confidence: 73%
“…Smart packaging utilizes sensors fabricated directly into packaging material in order to track information about its contents and environmental history, such as pH, temperature, gas levels, light exposure, and relative humidity [ 7 , 8 , 9 ]. Schaefer and Cheung [ 10 ] identify key challenges in the development of smart packaging, including fabricating thin film technology and reducing the environmental impact of unsustainable packaging materials.…”
Section: Introductionmentioning
confidence: 99%